(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Objective: To study the effectiveness and frequency of intraoperative complications of transurethral ureterolithotripsy (TUULT) in children with ureteral stones. Materials and methods: for the period from 2018 to 2022, transurethral ureterolithotripsy was performed in 253 children, whose average age was 9.8±4.1 years. The average stone size was 10.2±0.1 mm. Stones were located in the distal part in 76 (30.1%) cases, in the middle part in 70 (27.6%) children, and in the proximal part of the ureter in 107 (42.3%) patients. Results: the stone free indicator was 92.1%. Intraoperative complications were observed in 7.9% of cases. Ureteral perforation was observed in 4 (1.4%) cases, and conversion to traditional intervention was observed in 2 (0.6%) children. Conclusions: TUULT is an effective and safe method of removing stones from the ureter, regardless of the location of the stone.